PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN MEDIS & KEPERAWATAN DI RUMAH SAKIT XYZ - Puspita, Shandy; Nurhalim, Andres Dharma; Yohanes, Yohanes (STIE Wiyatamandala, 2023)
XYZ Hospital medical personnel and their colleagues are the focus of this study, which seeks to define and clarify how motivation affects performance. In this study, quantitative techniques were applied. The population of this study were 46 people who worked at the Gowa Regency Personnel and Human Resources Office. sampling from research using saturated sampling. Direct field studies by distributing questionnaires to participants became a data collection method. After that, the validity and reliability of the questionnaires obtained were evaluated. The findings indicate a sizable beneficial impact of motivating factors on job performance. Employee performance is greatly enhanced by the cleanliness aspect. Employee performance will be enhanced with motivator improvement factors and hygiene considerations. As a result, the attractiveness of employee performance in the medical field, especially at XYZ Hospital is supported by motivator factors and hygiene elements.